DETERMINATION OF THE RELIABILITY OF AIR POLLUTION MEASUREMENT DATA BASED ON VEHICULAR EMISSION RECOGNIZED AS CONCOMITANT IN ASTANA - Bissengaliyeva, Dariya; Amanzholov, Temirlan; Rakhimkul, Adina; Yedilkhan, Didar (Scientific Journal of Astana IT University, 2023)
Air pollution is a primary global concern due to its adverse effects on human health and the environment. Accurate air pollution measurement is crucial for developing effective control strategies and evaluating their impact. In Astana, vehicular emissions are recognized as a significant contributor to air pollution. This study aims to determine the reliability of air pollution measurement data in Astana by examining the impact of vehicular emissions on air quality to establish the accuracy of air pollution measurement methods in the city. The study will use a combination of monitoring and modeling techniques to quantify the contribution of vehicular emissions to air pollution in Astana. The monitoring component will involve the deployment of air quality monitoring stations throughout the city to measure levels of pollutants such as particulate matter (PM). The modeling component will use air dispersion models to simulate the dispersal of pollutants from vehicular emissions and predict their concentration levels in different parts of the city. The results of this research will provide insights into the effectiveness of existing air pollution control strategies and may inform future efforts to improve air quality in Astana. Based on the collected data for a certain period, a comparative table is built describing the difference between the actual data from the collection points of air emission indicators. The article will likely interest researchers and policymakers concerned with air pollution and its effects on human health and the environment. The critical point of the article is that air quality is affected not only by transport but also by other emissions.